2019
DOI: 10.1016/j.celrep.2018.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Mammalian COPII and COPI Vesicles

Abstract: Highlights d SILAC-based proteomics reveals the proteomes of mammalian COPI and COPII vesicles d ERGIC1, a putative cycling cargo adaptor, is an Sec24C/Ddependent cargo protein d CNIH4, an adaptor that controls GPCR exit from the ER, is an Sec24A-dependent client d COPI vesicles produced with different g/z-COP and Arf paralogs have similar proteomes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
117
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 76 publications
4
117
0
Order By: Relevance
“…In mammals and Arabidopsis, it has been proposed that different isoforms may be part of alternative coatomer complexes with different localization and perhaps different functions (Wegmann et al, 2004;Donohoe et al, 2007;Moelleken et al, 2007;Popoff et al, 2011;Gao et al, 2014). However, it has been recently reported that all of the isoforms of the mammalian COPI coat produce COPI-coated vesicles with strikingly similar protein compositions (Adolf et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals and Arabidopsis, it has been proposed that different isoforms may be part of alternative coatomer complexes with different localization and perhaps different functions (Wegmann et al, 2004;Donohoe et al, 2007;Moelleken et al, 2007;Popoff et al, 2011;Gao et al, 2014). However, it has been recently reported that all of the isoforms of the mammalian COPI coat produce COPI-coated vesicles with strikingly similar protein compositions (Adolf et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In these examples, the outcome of the mutations or treatment is a virtually complete block of ER/Golgi trafficking. This is however not expected in the absence of g1-COP, especially with the concomitant overexpression of g2-COP, as g1-COP-depleted cells are viable and g2-COPcontaining coatomer is as efficient in forming COPI vesicles as g1-COPcontaining coatomer in vitro 5,41 . One possibility is that g1-COP acts as a specific cargo receptor for proteins that are important for neuronal polarization.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that g-COP paralogs help maintaining protein concentration gradients across the Golgi stack, with g1-COP being more active at the ER/cis-Golgi interface. Proteomic analysis of COPI vesicles generated from various cell lines revealed that they mainly contain membrane trafficking regulating proteins, such as SNAREs (SNAP [soluble NSF attachment protein] receptor), and glycosylation enzymes 5 . The absence of one g-COP paralog may then affect the distribution or trafficking kinetics of such proteins across the Golgi, which might explain the phenotype of Copg1 KO cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been recent interest in quantifying the ab-solute numbers of proteins associated with intracellular vesicles. Proteomic estimates of protein composition have been obtained for COPII and COPI vesicles (Adolf et al, 2019), AP-1/clathrin-coated vesicles (Hirst et al, 2015) and for synaptic vesicles (Takamori et al, 2006;Wilhelm et al, 2014). In the latter two cases these data were used to build 3D models of an average vesicle which contains cargo.…”
Section: Introductionmentioning
confidence: 99%